2020
DOI: 10.21203/rs.3.rs-85624/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of prosocial behavior in multilayer populations

Abstract: Human societies include many types of social relationships. Friends, family, business colleagues, online contacts, and religious groups, for example, can all contribute to an individual's social life. Individuals may behave differently in different domains, but their success in one domain may nonetheless engender success in another. The complexity caused by distinct, but coupled, arenas of social interaction may be a key driver of prosocial or selfish behavior in societies. Here, we study this problem using mu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Yet we have found that, even for such networks, conversion of some bidirectional edges to unidirectional can rescue cooperation. An important implication is that asymmetric interactions provide an alternative method of modifying population structure to promote cooperation—besides severing old ties and building new ones, as has been explored in the bidirected setting ( 16 , 20 , 59 ) ( SI Appendix , Fig. S9 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet we have found that, even for such networks, conversion of some bidirectional edges to unidirectional can rescue cooperation. An important implication is that asymmetric interactions provide an alternative method of modifying population structure to promote cooperation—besides severing old ties and building new ones, as has been explored in the bidirected setting ( 16 , 20 , 59 ) ( SI Appendix , Fig. S9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature has revealed several key insights into this enigma ( 4 ). Population structure is perhaps the most widely discussed mechanism that can promote cooperation ( 5 , 6 ), and it has been studied by computer simulation ( 7 9 ), mathematical analysis ( 10 21 ), and experiments with human subjects ( 22 ). In structured populations individuals interact only with their neighbors—through either physical or social ties—and behaviors also spread locally.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has revealed several key insights into this enigma [4]. Population structure is perhaps the most widely discussed mechanism that can promote cooperation [5,6], and it has been studied by computer simulation [7][8][9], mathematical analysis [1,2,10,[12][13][14][15][16][17][18][19][20], and experiments with human subjects [22]. In structured populations individuals interact only with their neighbors -through either physical or social ties -and behaviors also spread locally.…”
Section: Introductionmentioning
confidence: 99%